The correlation between matriculation students’ lexical richness and their writing scores / Lee Hui Shein - Lee, Hui Shein (2013)
This research is carried out to study the relationship between the students’ lexical richness and their scores in Malaysian University English Test (MUET) composition written by 100 ESL students of Pusat Asasi Sains University of Malaya (PASUM). The use of lexis in writing was measured by Lexical Frequency Profile (LFP), a software developed by Laufer and Nation (1995) which is effective in assessing students’ lexical knowledge by categorising the words used in their writing according to four frequency bands: Band 1, Band 2, Academic Word List (AWL) and Not in the Lists (NIL). The percentages of AWL and NIL were added up and compared against the holistic scores given by their lecturers. Further, 14 item open-ended questionnaires were distributed to teachers to get feedback on their composition assessment procedures and also to find out the importance of lexis in writing. At the same time, a 21 item close-ended questionnaires to gather the students’ language background and perceptions on English language were distributed to the participants. Based on the results of this study, it was found that lexical richness plays an important role in determining the holistic scores of MUET written compositions.